Passive portfolio management by indexing: A performance analysis of high, medium and low capitalization indices in Mexico; Administración pasiva de portafolios mediante indexación: Un análisis del desempe\~no de los índices de alta, mediana y baja capitalización en México - Angel Samaniego; Luis Raúl Rodríguez Reyes (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
In a passive investing strategy through indexation, the portfolio performance will depend largely on the ability to choose the best index. In this paper, we study the performance of four of the main stock indices in Mexico with the intention of selecting the best one for a passive investing strategy. To solve this question, departing from the Sortino ratio, a definition of probability of success substitutes the average excess return over a target and the use of the maximum standard deviation on the negative target return. The new performance measure gives different results to those of the traditional Sortino ratio, with the IPC large cap being the best index for a passive strategy, in terms of risk-reward ratio and return target.
Keywords: G11; G14; 330; CAPM; information ratio; portfolio performance; Sortino ratio